Effets du stade de lactation sur la qualité nutritionnelle du lait de vache - Chikhi, Hadil (My University, 2024)
The stage of lactation has a significant impact on the physicochemical composition of cow's milk. The fat, dry matter, protein and mineral contents vary depending on the lactation phase. These variations also influence the acidity parameters of the milk. Physico-chemical analyzes are essential to understand and control these variations in order to guarantee the quality of milk and dairy products. The objective of studying the effects of lactation on the nutritional quality of cow's milk is to understand how the different phases of lactation influence the composition and properties of the milk produced. This understanding is crucial to optimize livestock management practices.